The uppermost Jurassic–Lower Cretaceous (Tithonian–Aptian) of the Raptawicka Gate section (High-Tatric succession, Poland): integrated stratigraphy and microfacies - Lodowski, Damian Gerard; Kowal-Kasprzyk, Justyna; Waśkowska, Anna; Granier, Bruno; Grabowski, Jacek (Acta Geologica Polonica, 2026)
This study presents the results of research conducted on material coming from the Raptawicka Gate section of the High-Tatric autochthonous succession (Kościeliska Valley, West Tatra Mts, Central West Carpathians, Poland). It utilizes biostratigraphic (calpionellids, calcareous dinocysts, foraminifers), quantitative microfacies, and geochemical (stable carbon and oxygen isotopes, main and trace elements concentrations) techniques. The section documents the transition between the Raptawicka Turnia Limestone (RTL) Fm and the Wysoka Turnia Limestone (WTL) Fm, with an erosional gap in between them. The RTL Fm part contains the Malmica–Remanei microfossil zones, and therefore belongs to the middle lower–upper Tithonian; the WTL Fm part contains a foraminiferal assemblage which characterizes the Barremian/Aptian transition and the lower Aptian, whereas the δ13C record largely conforms with the characteristics of Oceanic Anoxic Event 1a (OAE 1a). Correlation with the Giewont composite section (High-Tatric allochthonous unit) enables the presentation of a coherent record of Tithonian sedimentation in both areas. It also allows the inference that the topmost beds of the RTL Fm in the Raptawicka Gate section are younger than those in the Giewont composite section. Furthermore, the stratigraphic gap between the topmost Jurassic and the Lower Cretaceous sediments in the High-Tatric autochthonous cover (Raptawicka Gate) is significantly larger (topmost Tithonian–basal Aptian) than that within the Giewont Nappe (cf. topmost Tithonian–Berriasian). Ultimately, microfacies analysis allows the recognition of biotic events/processes documented in other western Tethys sections; these are thought to reflect major-scale environmental perturbations.